(untitled) (Majalah Kedokteran Bandung, 2021)
Kuhnle et al. has reported that Sunkist peels contain 36 µg/100 g wet weight of phytoesterogen. This study was designed to explore Sunkist peels’ potential to recover the infertility due to ovulation failure. This study was performed in June 2020 at the Pharmacology Laboratory, Universitas Prima Indonesia, on 25 rats. These rats were divided into five groups: Control, Standard, and Sunkist Peels Extract-I, II, and III that received 1 ml of 0.5% Sodium Carboxymethyl cellulose suspension, ethinyl estradiol 50 g/kgBW, 300 mg/kgBW, 450 mg/k BW, and 600 mg/kgBW of ethanol extract from Sunkist peel, respectively. Every 8-12 hours, the rat’s vagina were swabbed and smear into on object glass to be stained by 10% Giemsa and viewed at 40x and 100x magnifications. The leucocytes, especially neutrophils, epithelial cells, cornified and epithelial cells as well as the density of cells in vaginal swab were evaluated to determine the estrus cycle of the rats. The length of estrus phases was express as median (IQR) and analyzed using the Kruskall-Wallis test. The result of this study showed that the standard and highest dosage extract showed a significant extending of estrus and metestrus phases compared to the control group and significantly shortened diestrus phases. Hence, the highest dosage of Sunkist extract can prevent infertility by increasing the period of estrus cycle (ovulation) at the same level as the standard group.